2008
DOI: 10.1097/01.jcn.0000305094.20012.76
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance in People With Heart Failure

Abstract: Heart failure (HF) is associated with high levels of sleep disturbance and sleep disorders, including insomnia, periodic limb movements during sleep, and sleep disordered breathing. Recent studies underscore the importance of disturbances in sleep, a multidimensional biobehavioral phenomenon, to the pathophysiological processes associated with the development of HF, excess morbidity and mortality, and decrements in quality of life and functional performance. Managing disturbed sleep requires specific self-care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 80 publications
(88 reference statements)
3
39
1
3
Order By: Relevance
“…Heart failure (HF) is also associated with high levels of sleep disturbance and sleep disorders, including insomnia, periodic limb movements during sleep, and sleep disordered breathing. 18 One study was conducted by Johansson et al, on 331 elderly, to compare the prevalence of sleep disordered breathing and insomnia between elderly with heart failure and age and gender matched elderly without cardiovascular disease. They concluded that sleep disordered breathing, difficulties maintaining sleep and excessive daytime sleepiness were more common in elderly with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure (HF) is also associated with high levels of sleep disturbance and sleep disorders, including insomnia, periodic limb movements during sleep, and sleep disordered breathing. 18 One study was conducted by Johansson et al, on 331 elderly, to compare the prevalence of sleep disordered breathing and insomnia between elderly with heart failure and age and gender matched elderly without cardiovascular disease. They concluded that sleep disordered breathing, difficulties maintaining sleep and excessive daytime sleepiness were more common in elderly with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In this population, LVAD therapy has consistently resulted in superior survival and quality of life outcomes than use of maximum pharmacologic support [1][2][3][4][5][6][7]. Patients with advanced HF generally manifest fatigue at rest or with minimum exertion, bouts of psychological distress, and frequent sleep disturbance [8][9][10]. However, very little has been published on the course of these symptoms in LVAD recipients.…”
Section: Introductionmentioning
confidence: 96%
“…Additional research has shown how self-care behaviors provided an effective mechanism to reduce heart-failure patient expenses and to ameliorate negative patient health outcomes; however, those individuals with low SES still faced extenuating circumstances that exacerbated negative self-care (Macabasco-O'Connell, Crawford, Stotts, Stewart, & Froelicher, 2008). People with heart failure also suffered from disordered sleep, which had a negative impact on self-care (Redeker, 2008). …”
mentioning
confidence: 99%